Three Month Follow-Up of Patients With COVID-19 Pneumonia Complicated by Pulmonary Embolism - Calabrese, Cecilia; Annunziata, Anna; Flora, Martina; Mariniello, Domenica Francesca; Allocca, Valentino; Palma, Maria Ilaria; Coppola, Antonietta; Meoli, Ilernando; Pafundi, Pia Clara; Fiorentino, Giuseppe (Frontiers in Molecular Biosciences, 2022)
Three months follow-up of patients with COVID-19 pneumonia complicated by pulmonary embolism. Background. Previous studies have demonstrated persistent dyspnoea and impairment of respiratory function in the follow-up of patients recovered from COVID 19 pneumonia. However, no studies have evaluated the clinical and functional consequences of COVID 19 pneumonia complicated by pulmonary embolism. Objective. Aim of our study was to assess pulmonary function and exercise capacity in COVID-19 patients three months after recovery from pneumonia, either complicated or not by pulmonary embolism. Methods. It was a retrospective, single-centre, observational study involving 68 adult COVID-19 patients with a positive/negative clinical history of pulmonary embolism (PE) as a complication of COVID-19 pneumonia. Three months after recovery all patients underwent to spirometry, diffusion capacity of the lungs for carbon monoxide (DLCO) and 6 minutes walk test (6MWT). In addition, high-resolution computed tomography (HRCT) of the lung was carried out, and CT-pulmonary angiography (CTPA) only in PE + subgroup. Patients with previous diagnosis of PE or chronic lung diseases were excluded from the study. Results. 68 patients were included in the study, 24 with previous PE (PE+) and 44 without (PE-). In comparison with the PE- subgroup, PE+ patients displayed a FVC% predicted significantly lower (87,71 ±15,40 vs 98,7 ±16,7, p = 0.009) and a significantly lower DLCO% predicted (p = 0.023). In addition, a higher percentage of patients were dyspnoeic on exercise, as documented by a mMRC score ≥ 1 (75% vs 54,3%, p<0.001) and displayed a SpO2<90% during 6MWT (37.5% vs 0%, p<0.001). HRCT features suggestive of COVID-19 pneumonia resolution phase were present in both PE+ and PE- subjects without any significant difference (p =0.24) and abnormalities at CT pulmonary angiography were detected in 57% of PE+ subgroup. Conclusions. At the three months follow-up, patients recovered from COVID 19 pneumonia complicated by PE showed more dyspnoea and higher impairment of pulmonary functional tests in comparison with those without PE.